Exploring the phytochemicals and anti-cancer potential of the members of fabaceae family: a comprehensive review - Muhammad Usman; Waseem Razzaq Khan; Yousaf, Nousheen; Akram, Seemab; Murtaza, Ghulam; Abdul Kudus, Kamziah; Ditta, Allah; Rosli, Zamri; Rajpar, Muhammad Nawaz; Mohd Nazre, . (MDPI AG, 2022)
Cancer is the second-ranked disease and a cause of death for millions of people around the world despite many kinds of available treatments. Phytochemicals are considered a vital source of cancer-inhibiting drugs and utilize specific mechanisms including carcinogen inactivation, the induction of cell cycle arrest, anti-oxidant stress, apoptosis, and regulation of the immune system. Family Fabaceae is the second most diverse family in the plant kingdom, and species of the family are widely distributed across the world. The species of the Fabaceae family are rich in phytochemicals (flavonoids, lectins, saponins, alkaloids, carotenoids, and phenolic acids), which exhibit a variety of health benefits, especially anti-cancer properties; therefore, exploration of the phytochemicals present in various members of this family is crucial. These phytochemicals of the Fabaceae family have not been explored in a better way yet; therefore, this review is an effort to summarize all the possible information related to the phytochemical status of the Fabaceae family and their anti-cancer properties. Moreover, various research gaps have been identified with directions for future research.